Gatekeeping in interdisciplinary fields: the case of paleontology after the modern synthesis - Petino Zappala, María Alejandra (Synthese, 2025)
Setting standards for budding interdisciplinary fields is a crucial step in the acquisition of their identity and in making possible their coalescence and institutionalization. However, negotiating which of the epistemic standards of the original disciplines will be retained for the new field is not trivial. This paper explores how a bias towards the standards from one (now dominant) discipline can result in dynamics of gatekeeping against ideas and theories from other, now subordinate, ones. The emergent relationships of power can result in different varieties of exclusion or selective incorporation of ideas. More importantly, this can also bring about the loss of the identity and genuine contributions of subordinate disciplines within the new field. I illustrate this with the historical case of paleontology and its role within evolutionary biology after the establishment of the Modern Synthesis. I argue that a bias toward the standards of population genetics left paleontology in a subordinate position, ultimately leading to the dissatisfaction of paleontologists and their vocal rejection of the standards in place. To evidence this, I turn to the case of the Turkana Lake mollusks presented in 1981 as evidence for the theory of punctuated equilibria. The different standards in play at the time collided in the interpretation of these fossil sequences, reflecting broader trends in the reception of the theory itself. Inspecting the standards set for interdisciplinary fields as related to relations of power, I argue, can help not only understand problems faced by past synthetic efforts, but inform current and future attempts.